'A Tale of Silent Suffering': Wordsworth's Poetics of Silence and its Function of Reintegration. (10th March 2020) - Lo, Yimon
Abstract: Silence is an important aspect of Wordsworth's treatment of sound and the auditory imagination. With different emphases, a number of critics have attended to the significance of silence in Wordsworth's poetry. Various other scholars have addressed the notion of community in Wordsworth's silence. Their readings encourage a reappraisal of Wordsworth's poetics of silence as a mode of mournful reconciliation with forgotten communities. Alert to the ambiguities and contingencies in Wordsworth's consolatory vision, my argument reinforces the social and communal function of silence rather than evaluating its achievement of compensation or reassurance in respect of loss and suffering. My reading engages with the emergent critical interest in Wordsworth's use of negativity to offer a renewed perspective on how Wordsworth poeticizes the negative quality that silence lends to sound and mobilizes the idea of unattainable silence. Through debunking the conventional dualistic perception of sound and silence, my essay redefines the concept of auditory presence and absence to evaluate Wordsworth's poetics of silence in terms of its effectiveness as a medium for social, spiritual, and imaginative reintegration.